SBRT for oligoprogressive oncogene addicted NSCLC. (April 2017) - Basler, L.; Kroeze, S.G.C.; Guckenberger, M.
Highlights: Of patients with oncogene addicted metastatic NSCLC treated with TKI 15–47% develop oligoprogression. SBRT and concomitant TKI show favorable toxicity and high local tumor control rates. SBRT of OPD restores TKI sensitivity enabling TKI treatment beyond progression. Defining OPD and sequencing of treatment options need refinement in prospective trials. Abstract: Lung cancer is one of the leading causes of cancer death in men and women and treatment outcome continues to lag behind other common cancer types. A subset of lung adenocarcinoma patients exhibit a somatic mutation in EGFR or an ALK rearrangement. In these patients, targeted TKI therapy results in higher response rates, improved PFS and reduced side effects compared with platinum-based chemotherapy. Despite initial activity of the TKIs, ultimately all patients present with disease progression after about a year on TKI therapy due to resistance development. About 15–47% of patients present with limited oligoprogressive disease (OPD): such patients show only a limited number of metastases with progression in radiological imaging. Radical local treatment to all oligoprogressive lesions is thought to eradicate the de-differentiated clones and restore overall sensitivity of the metastatic disease. Retrospective studies suggest that aggressive local treatment using stereotactic body radiotherapy (SBRT), surgery or others can be used to eradicate TKI-resistant subpopulations enabling prolonged TKI treatment "beyond progression", which may lead to increased PFS and overall survival. This review focuses on the biological background of resistance development, systemic and local treatment options with a focus on SBRT, as well as challenges in defining the state of OPD and current clinical studies in oligoprogressive oncogene addicted NSCLC.